Analisis dan penerapan dasar-dasar pengembangan kurikulum berdasarkan kebutuhan masyarakat - Fudhla, Mahmudatun; Kartika, Adhisti Malla; Ahmad, Fauzi; Suti’ah, Suti’ah (Maliki Interdisciplinary Journal, 2024)
The development of educational curricula has an important role in preparing future generations who have abilities and skills that suit the needs of society. A good curriculum must consider various aspects, including the needs, demands, aspirations and problems of society. This analysis focuses on the basics of curriculum development based on community needs and its application in curriculum development. Developments in science and technology also influence the curriculum, which must be able to accommodate and anticipate these changes. A good curriculum must develop students’ critical thinking skills and adapt to change. Analysis of community needs in curriculum development is carried out through various approaches, such as needs surveys, competency studies, and task analysis. The basics of curriculum development include philosophical, psychological, socio-cultural, and scientific and technological foundations. The implementation of a community needs-based curriculum emphasizes the integration of schools and communities to achieve teaching goals. This curriculum aims to make students familiar with their environment, independent, and have skills that are relevant to society’s needs. The characteristics of this curriculum include learning that is oriented towards students’ interests for their future lives. The results of this analysis show that a community-based curriculum can improve the quality of education and prepare a generation that has abilities and skills that suit society’s needs.